An environmental study of the effect of toxicity of some heavy metals on the survival and survival of carp (Cyprinus carpio L.) fingerlings taken from the Martyr's Monument pond (Iraq - Baghdad) (Journal of the College of Basic Education, 2022)
The present study was aimed to expose the common carp fish fingerlings Cyprinus carpio L. with the weight of (200 ± 10) milligram and length of (2-3) cm to equal Concentrations of (0.5, 1, 1.5) mg/l of lead, cadmium and copper for 10 days. Toxicity study of these elements as survival ratio and lethal time 50%, 100%. During this study,has been the measurements for the physical and chemical factors of the water was detected for the fish experiments ( pond water,Tap water, Tap water after adding toxic elements). These factors were the following (water temperature, pH and electrical conductivity and total hardness and concentration of calcium and magnesium, and dissolved oxygen) they ranged were between(24 -25.5) C0, (8.2-7.9) ,( 797-3000) μS\cm, (265-1010) mg/l , (59.25-200) mg/l , (28.5-121) mg/l, (9-11) mg/l. respectively. The results showed from fingerlings of (Cyprinus carpio L.) that are exposured to experimental concentrations(0.5, 1, 1.5) mg /l of lead showed that no any mortality. Were recorded after the fingerling exposuring to the cadmium poisoning as (1, 1.5) mg /l the LT50% for (1) mg / l was recorded in the 9th day while the LT50% for (1.5 mg / L) in the 6th day. and no any LT100% gained for the (0.5, 1, 1.5)mg /l concentration.there are no mortality with this metals poisoning at the concetration of 0.5 mg /l. After the copper poisoning at the concentration as (0.5, 1, 1.5) mg /l the LT50% was at the day 7th and no any LT100% gained for the 0.5 mg /l concentration.at the(1) mg / l concentration for the same elements, The LT50% was gained at the 5th day.While the LT100% was gained at the 8th day . With the 1.5 mg /l concentration for the same elements, the LT50% was gained at the 3th day. While the LT100% was gained at the 5th day